Occupational allergy to fruit flies (Drosophila melanogaster) in laboratory workers. Issue 6 (30th December 2016) - Jones, Meinir; Blair, Sue; MacNeill, Stephanie; Welch, Jennifer; Hole, Alice; Baxter, Peter; Cullinan, Paul
Abstract : Objectives: Drosophila melanogaster (the 'fruit fly') is commonly used in genetic research, but there is only one report of IgE-associated allergy in exposed workers. 4 newly identified cases prompted us to examine the extent of this problem in a university laboratory. Our aim in this study is to determine the prevalence and determinants of sensitisation to fruit flies in a population of exposed workers. Methods: In a cross-sectional study, we surveyed 286 employees working in a department carrying out research involving D. melanogaster . Sensitisation was assessed by specific IgE measurement in serum and examined in relation to symptoms and to estimated exposure to fruit flies. Results: The overall prevalence of specific sensitisation was 6% with a clear relationship to increasing frequency/intensity of exposure (p trend<0.001). Work-related eye/nose, chest or skin symptoms were reported by substantial proportions of participants but for most of these there was no evidence of specific sensitisation to fruit fly. The overall prevalence of any work-related symptoms and sensitisation was 2.4%, rising to 7.1% in those working in high exposure groups. Conclusions: We were able to demonstrate, for the first time, a clear exposure–response relationship between fruit fly exposure and specific sensitisation. Facilities housing fruit flies should carefully consider methods to reduce exposure levels in the workplace.